Weak intermolecular interactions in a series of biologically active 4′‐methylthio‐trans‐stilbenes. Issue 2 (25th January 2022) - Grześkiewicz, Anita M.; Stefański, Tomasz; Dutkiewicz, Zbigniew; Kubicki, Maciej
Abstract : The crystal structures of nine methoxy‐substituted 4′‐methylthiostilbenes, which are potential inhibitors of human recombinant cytochrome P450 enzymes, were determined. The geometries were compared with those found during docking studies at the active site of the receptor and some relevant differences were identified. Abstract : The crystal structures of nine methoxy‐substituted 4′‐methylthiostilbenes, which are potential inhibitors of human recombinant cytochrome P450 enzymes, were determined. These compounds included two mono‐methoxy‐substituted derivatives: 2‐methoxy‐4′‐methylthio‐ trans ‐stilbene {systematic name: 1‐[( E )‐2‐(2‐methoxyphenyl)ethenyl]‐4‐(methylsulfanyl)benzene} (1 ) and 3‐methoxy‐4′‐methylthio‐ trans ‐stilbene (2 ), both C16 H16 OS; four dimethoxy derivatives: 2, 3‐dimethoxy‐4′‐methylthio‐ trans ‐stilbene (3 ), 2, 5‐dimethoxy‐4′‐methylthio‐ trans ‐stilbene (4 ), 3, 5‐dimethoxy‐4′‐methylthio‐ trans ‐stilbene (5 ) and 2, 4‐dimethoxy‐4′‐methylthio‐ trans ‐stilbene (6 ), all C17 H18 O2 S; and three trimethoxy compounds: 2, 4, 5‐trimethoxy‐4′‐methylthio‐ trans ‐stilbene (7 ), 3, 4, 5‐trimethoxy‐4′‐methylthio‐ trans ‐stilbene (8 ) and 2, 4, 6‐trimethoxy‐4′‐methylthio‐ trans ‐stilbene (9 ), all C18 H20 O3 S. The geometries of the compounds in the crystal structures were compared with those found during docking studies at the active site of the receptor, and some relevant differences were identified. Intermolecular interactions were analyzed using three different methods. First, the (3, −1) critical points of the gradient field of the electron density were identified, and then the appropriate contacts were analyzed using their geometrical characteristics and interaction energy calculations. The results confirmed the importance of weak delocalized interactions in the construction of the crystal structures, and the results of different methods (PIXEL and DFT) were comparable in the absence of strong well‐defined intermolecular interactions.